Studi Kontrastif Kalimat Verbal Bahas Arab-Bahasa Indonesia dan Implikasinya dalam Pengajaran Nahwu - Maman Abdurahman (Buletin Al-Turas, 2007)
This paper aims to describe the similarity and the difference ofArabic and Indonesian verbal sentence structure. To get this goal used thecontrastive and comparative methods. The material object is limited by verbal sentence structure with it contains 1) single transitive sentence 2) double transitive sentence 3) intransitive sentence 4) semi transitive sentence, and passive sentence. The data resources taken from five Arabic and Indonesian grammar/syntax books chosen and analyzed quantitatively, such as describing. selecting, contrasting. and concluding. The result of analyzed data concludes some of syntax similarities between Arabic and Indonesian verbal sentence structure. This difference looks that the Arabic active verbal sentence structure more variety than Indonesian and Indonesianpassive verbal sentence structure more variety than Arabic.